Síndrome del Impostor en Mujeres: Estudio transversal en cinco países latinoamericanos - Martínez Moreno, Alma Gabriela (2025)
Imposter syndrome is a psychological state in which people express doubts about their achievements and abilities. The relationship between imposter syndrome and sociodemographic and psychological variables was evaluated through a cross-sectional study in women residing in Argentina, Chile, Colombia, Mexico and Peru. A questionnaire was applied, Imposter Phenomenon Scale, Depression Scale, Anxiety Inventory and Insomnia Severity Index. 75% present imposter syndrome, 70% anxiety, 50% insomnia and 36% depression. Two multivariate models show that being a researcher or having a managerial position, children and being married are predictors for imposter syndrome. This situation can hinder their growth and make it difficult for them to accept management positions.